Le fabuleux destin du quotidien = The fabulous destiny of the quotidian - Foulon, Françoise; Wenes, Veerle; Busine, Laurent; Gielen, Denis; Bouchez, Hilde; Musée des arts contemporains (Hornu, Belgium); Grand-Hornu (Firm) (Hornu : MAC's : Grand Hornu Images, 2010)
Between art and design, there is an ebb and flow of thought which reveals their common points as well as their essential differences. Contemporary creators frequently combine genres and pass from one to the other, even combining them in their works, such as they can no longer be defined unilaterally and conclusively. This book, published to coincide with an exhibition at Grand-Hornu in 2010, includes contributions by some ten authors from various backgrounds, in both art and design. They envisage this situation based on historic, analytical and even poetic concepts.
Art et design : retour sur une relation centenaire = Art and design : reflection on a centennial relationship / Yoann Van Parys -- Design et art : un mariage arrangé = Design and art : an arranged marriage / Marie Pok -- Que le vrai designer se lève! = Will the real designer please stand up! / Hilde Bouchez -- L'objet usuel, hantise de l'œuvre d'art = The fear of art for the everyday object / Marc Holthof -- Sortilèges de l'objet = The spellcraft of the object / Françoise Foulon -- Le bon usage = Correct usage / Laurent Busine -- Prendre part : les objets et les affects = Taking part : objects and affects / Isabelle de Visscher-Lemaître -- La table des tables = Table of tables / Sylvain Busine.
Text in French and English.
Catalog of an exhibition held at the MACs (Museum of Contemporary Art) and Grand-Hornu Images, Feb. 7-May 23, 2010, to celebrate the bicentenary of the Grand-Hornu site.
"Art & design"--Cover.
boek